Compensatory strategies below the behavioural surface in autism: a qualitative study - Livingston, Lucy Anne; Shah, Punit; Happé, Francesca (The Lancet. Psychiatry, 2019)
Little is known about the compensatory profile in autism; that is, people with autism spectrum disorder who show few symptoms in their behavioural presentation, despite continuing to report autism-related cognitive difficulties or differences. Even less is known about the specific compensatory strategies that these individuals use to disguise autism at the behavioural surface, both in the clinic and everyday life. It is also currently unclear whether individuals without a formal autism diagnosis, but experiencing autistic-like difficulties, use similar compensatory strategies, potentially enabling them to sit below the diagnostic threshold. This study aimed to investigate social compensatory strategies, and their effect on diagnosis and clinical outcome, in adults with and without autism. In this study, individuals aged 18 years or older who responded to a study advert that was distributed worldwide via social media and the UK National Autistic Society formed a convenience sample. Participants self-reported their use and experiences of compensatory strategies using an online platform. Novel analyses, including a qualitative thematic approach, were used to interpret their responses and gain insight into compensatory strategies in autism. Between Oct 19, 2017, and Jan 2, 2018, 136 adults (58 had a clinical diagnosis of autism, 19 self-identified but were not formally diagnosed as autistic, and 59 were not diagnosed or self-identified, but nevertheless reported social difficulties) completed the online study questions. The findings suggested that there are multiple compensatory strategies with distinct characteristics, individual and environmental factors that modulate compensatory strategy use and success, positive (social relationships, independence, employment) and negative (poor mental health, late diagnosis) outcomes associated with compensatory strategy use, and that individuals without a diagnosis use compensatory strategies that are qualitatively similar to individuals with a diagnosis. Increased awareness and measurement of compensatory strategy use in autism should guide future diagnostic guidelines, towards improved diagnostic accuracy and support for people with autism spectrum disorder whose cognitive difficulties are not immediately evident in observable behaviour. UK Medical Research Council and UK National Institute for Health Research.